form and content - Lidin, Konstantin (project baikal, 2023)
About a hundred years ago, a period of unprecedented flourishing and multiplication of theoretical models, which treated architecture from a variety of positions, began. The poetic whims of modern and the laconic volumes of modernism, the irony of postmodernism, the paradoxical games of structuralists, the mathematical formulas of parametricism, and many other attempts to use theories adopted from other sciences show that one cannot do without theory. Does architecture have its own set of methods for analysing and synthesising meanings (which, in fact, forms a science separate from other sciences)? Or is architectural theory a disorderly mishmash of contradictory approaches, methods, individual insights and incomprehensible white spots? In this block, we have collected several examples of contemporary theoretical analysis and attempts to realise the state of architectural theory in general. As usual, we have more questions than answers.